Correction: Elalouf et al. Bioinformatics-Driven mRNA-Based Vaccine Design for Controlling Tinea Cruris Induced by Trichophyton rubrum. Pharmaceutics 2024, 16, 983 - Amir Elalouf; Hanan Maoz; Amit Yaniv Rosenfeld (MDPI AG, 2024)
In the original publication [...]